Whispered lies - Kenyon, Sherrilyn, 1965-; Love, Dianna (New York : Pocket Books, 2009)
Bureau of American Defense operative Carlos Delgado must join forces with informant Gabrielle Saxe--a woman he can neither trust nor resist--to uncover a deadly plan that risks countless lives and threatens economic chaos just days before the U.S. presidential election.
Keywords: Terrorism -- Prevention -- Fiction; Romantic suspense fiction